2013
DOI: 10.3389/fimmu.2013.00163
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Regulatory T Cells in the Biology of Graft Versus Host Disease

Abstract: Graft versus host disease (GVHD) is the major complication of allogeneic hematopoietic stem cell transplantation. GVHD is characterized by an imbalance between the effector and regulatory arms of the immune system which results in the over production of inflammatory cytokines. Moreover, there is a persistent reduction in the number of regulatory T (Treg) cells which limits the ability of the immune system to re-calibrate this proinflammatory environment. Treg cells are comprised of both natural and induced pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 88 publications
(116 reference statements)
1
88
0
5
Order By: Relevance
“…+ FoxP3 + T regs detected in CD4 + ATs Tregs have been found to exert vital functions in restricting aGVHD by suppressing the proliferation or induce the apoptosis of Teffs (Beres and Drobyski 2013). It remains controversial whether CB contains a larger number of natural Tregs (nTregs) than APB.…”
Section: Alloantigen-induced (Allo-induced) Cd25mentioning
confidence: 99%
“…+ FoxP3 + T regs detected in CD4 + ATs Tregs have been found to exert vital functions in restricting aGVHD by suppressing the proliferation or induce the apoptosis of Teffs (Beres and Drobyski 2013). It remains controversial whether CB contains a larger number of natural Tregs (nTregs) than APB.…”
Section: Alloantigen-induced (Allo-induced) Cd25mentioning
confidence: 99%
“…The transplant of blood mobilized using CDX-301 plus AMD3100 into lethally ablated mice was also shown to be associated with a survival advantage [74]. Moreover, the CDX-301 plus AMD3100 combination effectively mobilized regulatory T cells (T reg ), which may have protective effects against graft vs host disease (GvHD) after allogeneic transplantation (Reviewed in [75]). Indeed, transplantation of irradiated recipients with blood mobilized with CDX-301, either alone or in combination with AMD3100 correlated with enhanced survival in an allogeneic transplant setting [74].…”
Section: Cytokines Growth Factors and Hormonesmentioning
confidence: 99%
“…Graft versus host disease (GVHD) is the main complications following allo-HSCT. GVHD is primarily a donor T cellmediated syndrome whereby T cells in the graft elicit an immune response, resulting in host tissue damage [1,2]. Knowledge of the immunobiology underlying GVHD has advanced by virtue of immunology research in animal models, as well as clinical observations.…”
Section: Introductionmentioning
confidence: 99%
“…Since GVHD is characterized by the loss of tolerance and the development of autoimmune manifestations, it is reasonable to indicate that a deficiency in regulatory T (Treg) cells reconstitution plays a critical role in GVHD pathophysiology and might participate in mediating GVHD and graft-versus-leukemia (GVL) effect after allo-HSCT [4,5]. The Treg cells, which identified suppressive population of CD4+ T cells that expressed high levels of the IL-2 receptor α-chain (CD25) formerly known as suppressor T cells, are a subpopulation of T cells which modulate the immune system, maintain tolerance to self-antigens, and abrogate autoimmune disease [1,6,7]. Mouse models have suggested that modulation of Treg cells can treat autoimmune disease and cancer, and facilitate organ transplantation [1,3,8], while the molecular mechanism of Treg cells is still unclear.…”
Section: Introductionmentioning
confidence: 99%